Od Valerie do Fausta i Wolnego strzelca: kilka uwag o intertekstualnej strategii I części Dziadów - Fiećko, Jerzy (Przestrzenie Teorii, 2019)
The author analyses intertextual relations in the first and final section of part of “Forefathers’ Eve” (Dziady), and treats them as an element of Mickiewicz’s strategy of anchoring his own work in the system of dialogue with renowned Western cultural works of the time. This dialogue takes the form of a polemic against the sentimental French models akin to de Krüdener’s “Valerie” and the Sturm und Drang movement, which was open to issues of characterisation and early German romanticism. In the first part of the book, which focuses on an analysis of the Maiden’s monologue, the author discerns a mechanism of references to Barbara Julianna de Krüdener’s novel “Valerie” and “The Sorrows of Young Werther”, with which the baroness engaged in an open dispute. The second part focuses on the character of Gustaw and his conversation with the Black Hunter, with an analysis of likely connections with the Weber/Kind’s opera “The Marksman” and the plays of Goethe and Klingemann with the same main title “Faust”.